FEATURES OF INTERIOR DESIGN OF SOCIAL HOUSING - Abyzov, V. A.; Brazhnikova, I. S.; Vyshnevska, O. V.; Ryshkevych, N. O. (Art and Design, 2021)
The purposeof the study are analysis and definition of the main functional-planning, artistic and aesthetic features of the formation of interiors of social housing and development of proposals for their modern design solutions. Methodology. Theoretical and practical research methods were used, namely analysis of scientific and popular literature on the research topic, generalization of approaches to functional-planning and stylistic solutions of social housing based on analysis of design experience, experimental computer modeling using ArchiCAD and 3DsMax. Results. Based on the analysis of research and modern practice of formation of social housing, the methods of functional-planning and artistic-aesthetic organization of the internal environment of social housing and its subject-spatial content are revealed. Features and examples of rational interior design solutions for small apartments are considered. The scientific novelty lies in the generalization of previous research on this topic and the identification of functional and planning features of the formation of the subject-spatial environment of social housing of small apartments and providing suggestions for the design of their interiors. Practical significance. The results of the study can be used in their introduction into the modern practice of designing social housing with economical small apartments and in the development of interiors of their internal subject-spatial environment.